2018
DOI: 10.21767/2471-8203.100037
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Objective Activity Monitoring in Off-Site Follow-Ups Post-Bariatric Surgery

Abstract: Title: The Potential Role of Objective Activity Monitoring in Off-Site Follow-Ups Post-Bariatric Surgery.Background: Weight gain and attendance at follow-up visits after bariatric surgery are of great concern for the multidisciplinary care team. Geography and schedules make attending follow-up visits increasingly difficult as time after surgery goes on. Recently, inexpensive commercially available activity monitors have become more common place, making information concerning physical activity and sedentary beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Previous reports using smartphone-based accelerometers, which track a patient's daily steps, have demonstrated that such mobility data can successfully quantify and characterize patient outcomes after surgery. [6][7][8][9] The relationship between patient mobilization and surgical outcomes is especially salient in spine surgery, given the nuanced impact lumbar spine pathology can have on preoperative and postoperative patient activity. 10 For example, greater physical activity after lumbar spine surgery is generally associated with both improved outcomes 11 and increased pain.…”
mentioning
confidence: 99%
“…Previous reports using smartphone-based accelerometers, which track a patient's daily steps, have demonstrated that such mobility data can successfully quantify and characterize patient outcomes after surgery. [6][7][8][9] The relationship between patient mobilization and surgical outcomes is especially salient in spine surgery, given the nuanced impact lumbar spine pathology can have on preoperative and postoperative patient activity. 10 For example, greater physical activity after lumbar spine surgery is generally associated with both improved outcomes 11 and increased pain.…”
mentioning
confidence: 99%